A dictionary of philosophy of religion - Taliaferro, Charles; Marty, Elsa J. (Continuum, 2010)
This is an indispensable and comprehensive resource for students and scholars of philosophy of religion. ""A Dictionary in Philosophy of Religion"" is an indispensable source for students and scholars. Covering historical and contemporary figures, arguments, and terms, it offers an overview of the vital themes that make philosophy of religion the growing, vigorous field that it is today. In addition to the entries co-authored by Taliaferro and Marty, leading scholars in philosophy of religion have contributed to the Dictionary, including Brian Davies, Pamela Sue Anderson, Paul Draper, Jerry Wa